Development of white common beans for the processing industry in East Africa: adaptability, resistence to selected diseases, cooking time and canning quality - Amongi, Winnyfred; Kato, F.; Male, A.; Musoke, S.; Acam, C.; Kabwama, A.; Nakyanzi, B.; Sebuliba, S.; Williams, M.; Mbiu, J.; Baguma, G.; Mukankusi, C. (African Journals Online, 2021)
Common bean (Phaseolus vulgaris L.) provides dietary protein, ener gy, fiber, and micronutrients, especially iron and zinc to over 800 million people inAfrica and LatinAmerica. The crop has various seed types. White beans are very popular for the processing industry. This study aimed to investigate the agronomic performance, canning quality , cooking time (COOKT) and response to root rots (Fusarium cuneirostrum and Pythium ultimum ) and angular leaf spot (ALS; Pseudocercospora griseola) diseases among 151 drought tolerant small and large seeded white bean genotypes from trials conducted between 2013 to 2018 in EastAfrica. Significant (P<0.001) differences existed among the genotypes for response to the three pathogens, COOKT and canning quality traits. Resistance to each of the pathogens was expressed in 24-75% of the genotypes, while dual resistance to any two pairs of the pathogens occurred in 10-44% of the genotypes. Four genotypes; ICNBunsixSxB405/4C- 1C-1C-88, RAZ-11, ETSNAP18 and ETSNAP3 expressed resistance to the three pathogens but had COOKT of 46-56 minutes (based on a Matson cooker), and below average canning quality. They are recommended as sources of diseases resistance but could be further improved for COOKT and canning quality. Sixty-eight genotypes had COOKT<50 minutes while 24 expressed good to excellent visual canning quality. Some phenotypes: RAZ-120, RAZ36-Caballero, NavyLine-60, NavyLine-25, ZABR16573-25F22, ZABR16575-60F22, ETSNAP33, Bifortsmallseeded-15 and ZABR16574-37F22, that were cooked in <45 minutes, exhibited good to excellent canning quality and expressed resistant to intermediate diseases resistance responses. These may be used as parental lines and/or fast tracked for variety release through regional trials.